Clinical professionals’ perceptions of laboratory procedures and their use of laboratory investigations in Saudi Arabia 2024 - Abdulrahman Salem Fodail Al ghamdi; Azzah Ahmed Mordhi Alzahrani; Faiza Ahmed Abdullah Daeeth; Tareq Ali ALZahrani; Saleh Yateim Abdulrhman Alghamdi; Saeed Masoud Saeed Alghamdi; Jamaan Ali Qathan Alghamdi; Rashad Rashed Alrashed; Abdullah Hamdan Mobark Alahmadi; Abdullah Salem Jubran Aljohani; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: A key component of getting the right clinical diagnosis for patients is laboratory testing. Nonetheless, it is still usual to order pointless or improper laboratory tests, which results in the use of both people and material resources.In recent years, the outcomes of laboratory tests have grown more and more important in patient care. Laboratory tests have been and will remain a crucial component of clinical practice. Physicians concentrate on the more general topic of protocols as a way to handle medical information. The study aims: To assess theutilization of lab investigations by clinicians and also to take their perspective of lab practices so that it would help as a feed back and aids in improvement of lab services. Materials and Methods: A cross sectional study was used. A questionnaire consisting of 15 questions was distributed to 30 clinicians and their response to different questions was converted to percentage scale. Results:The majority of clinicians (86.6%) frequently used lab services. 33.3% of respondents claimed that lab services were overused, and they cited the need for early diagnosis and medical legal reasons as justifications. Of them, 10% had never heard of quality control, and 33.3% had heard the word but were unaware of its significance. According to 76.6% of clinicians, the MBBS curriculum should cover quality control and fundamental lab procedures. Conclusion: Clinical professionals frequently use laboratory services. According to the majority, the lab services are being used appropriately. Quality control and fundamental laboratory procedures must be incorporated within the MBBS curriculum.